Estimates of evapotranspiration from contrasting Wisconsin peatlands based on diel water table oscillations. Issue 4 (2nd March 2017) - Watras, C.J.; Morrison, K.A.; Rubsam, J.L.; Buffam, I.
Abstract: Evapotranspiration rates (ET) from contrasting Wisconsin bogs (one forested bog, one open bog) were compared over 4 years by analyzing diel oscillations of their water tables. Daily rates of ET from peatlands were also compared to rates of evaporation (E) from encircled bog ponds. We hypothesized that ET would be higher in the forested bog due to the greater leaf area index of forest canopy relative to moss and ericaceous shrubs. We also hypothesized that ET in peatlands would exceed the physical process of E from encircled ponds. Field data supported the first hypothesis, but the second only proved true for the forested peatland. Daily estimates of peatland ET varied widely, ranging from 1 to >10 mm/d; but average ET was higher in the forested peatland (4.04 vs. 3.09 mm/d; p < .01). Average ET in the forested peatland was also higher than E during summer (4.04 vs. 3.31 mm/d; p < .05); whereas in the open peatland, average ET was slightly lower than E for all measured seasons ( p < .01). Methodologically, the performance of three equations used to estimate ET from daily water table fluctuations was similar. The specific yield of peat (S*y), which is a critical variable in all three equations, was found to be an exponential function of water table depth; and absent an empirically derived S*y, errors in estimates of peatland ET can be large. Given landscape composition across this northern temperate region (13% lakes, 20% peatland, and 54% upland forest) and estimates of forest ET gleaned from the literature, our findings suggest that the regional feedback of water to the atmosphere increases from open waters to peatlands to upland forest, consistent with prior observations that the biological process of transpiration dominates continental ET.